PENGARUH SITUASIONALTERHADAP KECEMASAN MAHASISWA PROGRAM STUDI D III KEPERAWATAN MENGHADAPI UJIAN SKILL LABORATORIUM: STUDI MIXED METHODS - Yulifah Salistia Budi; Shanti Wardaningsih; Moh. Afandi (IJNP (Indonesian Journal of Nursing Practices), 2016)
Purpose: The purpose of this study wasto determine the influence of situational to anxiety and anxiety levels of diploma nursing students at Institute of Health Sciences Banyuwangi in the skill exam laboratory. Method: This study used a mixed methods with explanatory sequential models, by involved were students, lectures and the lab staff in January, 16th-20 th 2017. The quantitative analysis used Kruskall Wallis test, followed by a qualitative analysis of manually categorizing data then inferred from both the analysis. Result: The result of quantitative method that the majority of respondents were in mild anxiety levels, by Kruskall Wallis obtained a not significant influence on situational to anxiety of Diploma Nursing Student in the exam skills lab. Qualitative results indicated to four themes: noisy, temperature skill room, timing in the exam skill lab and preparation of the situational. Conclusion: that the majority of respondents were in mild anxiety levels and there’s the influence of situational to anxiety in diploma nursing students. By that results, to have follow-up for students, examiner, and the lab staffs from relevant parties concerned to overcome the student’s anxiety toward the lab skills exam related in atmosphere skill lab exam.